Do ostriches live in Central Europe? : Normalizing the Russian attack on Ukraine in the Visegrád Four - Kazharski, Aliaksei (Journal of Regional Security, 2023)
In terms of studying discursive normalization of the Russo-Ukrainian war the Visegrád Four (V4) present us with a stimulating case for regional comparisons. On the one hand, there are obvious intra-regional differences that are rooted in specific identitary legacies and the resulting strategic cultures, which can come into a sharp clash, as they did for example in the case of the public Polish-Hungarian split over the 2022 invasion. Against this background, however, there are also telling points of convergence that arguably have to do with the structural position of the V4 in the European international order and the related historical experience.